2011
DOI: 10.1007/s10661-011-2093-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pendimethalin and quizalofop on N2-fixing bacteria in relation to availability of nitrogen in a Typic Haplustept soil of West Bengal, India

Abstract: An experiment was conducted under laboratory conditions to investigate the effect of two systemic herbicides viz., pendimethalin and quizalofop, at their recommended field rates (1.0 kg and 50 g active ingredient ha(- 1), respectively) on the growth and activities of non-symbiotic N(2)-fixing bacteria in relation to mineralization and availability of nitrogen in a Typic Haplustept soil. Both the herbicides, either singly or in a combination, stimulated the growth and activities of N(2)-fixing bacteria resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Shukla and Das [76] reported that Nitrosomonas population at 1-3 ppm while Nitrobacter population at 1-2 ppm of pendimethalin were comparable with that in control, indicating no or very little effect of pendimethalin even at these very high doses of application. Das et al [17] observed that pendimethalin and quizalofop applied at recommended rates solely or in combination stimulated aerobic nonsymbiotic N-fixing bacteria. The MC and biofilms may respond to herbicides/pesticides in similar way as the individual microbe does, and this opens up the possibility of their use in modern agriculture.…”
Section: Responses Of Microbes/microbial Consortia To Pesticidesmentioning
confidence: 99%
“…Shukla and Das [76] reported that Nitrosomonas population at 1-3 ppm while Nitrobacter population at 1-2 ppm of pendimethalin were comparable with that in control, indicating no or very little effect of pendimethalin even at these very high doses of application. Das et al [17] observed that pendimethalin and quizalofop applied at recommended rates solely or in combination stimulated aerobic nonsymbiotic N-fixing bacteria. The MC and biofilms may respond to herbicides/pesticides in similar way as the individual microbe does, and this opens up the possibility of their use in modern agriculture.…”
Section: Responses Of Microbes/microbial Consortia To Pesticidesmentioning
confidence: 99%
“…As compared to untreated control, the higher stimulation of microbial population was manifested at lower concentrations of the herbicides, being the highest under thiobencarb (54.0%) followed by pretilachlor (25.2%), while the threefold increase in concentration of the herbicides over the field application rates exerted less stimulatory effect towards the growth and proliferation of aerobic non-symbiotic N 2 -fixing bacteria in soil. The significant rise in microbial population during 15-30 days followed by a gradual decrease up to 60 days of sampling, pointed out that aerobic non-symbiotic N 2 -fixing bacteria preferably utilized the incorporated herbicide residues and their degraded fractions as their source of carbon, energy and other nutrient elements for their cellular metabolism (Debnath et al, 2002;Das et al, 2012b). Consequently, the amount of herbicidal residues was gradually depleted in the later incubation periods, resulting in less number of bacterial colonies in the subsequent sampling days.…”
Section: Effect On Microbial Populationmentioning
confidence: 99%
“…On the other hand, some research evidences exhibit that herbicides show stimulating effect on growth and metabolism of non-symbiotic nitrogen fixing bacteria [11] and phosphate solubilizing microbes [4]. At this juncture, this study is necessary to identify whether herbicide application suppress or enhance/ stimulate the soil microbial population.…”
Section: Introductionmentioning
confidence: 99%